Pengembangan Media Pembelajaran Audio Berbasis Podcast Pada Materi IPS di SD - Fadia Tri Ananda; Faradila Ayu Ramadhani; Zulfa Putri Fadilah (UIN Fatmawati Sukarno Bengkulu, 2022)
This research utilizes digital media to support the effectiveness of classroom learning. Podcast digital learning media was chosen because it was considered easy for students to access. A podcast is a distribution of audio recordings made through the process of audio recording and editing which is then delivered over the internet. Using quality data analysis and Research and Development research methods, researchers develop and revise podcast products based on field test results. Qualitative data is taken from researcher questions and responses or validations from experts and class VI learners regarding the products developed. Through model of development addie was consisting of analysis , design , development , implementation , and evaluation .Field test results obtained that media is learning podcast suitable and effective for used as a medium learning .So , it is expected that the development media podcast to the matter is social class , educators and school tuition can take advantage of digital media to support the effectiveness of learning activities.